2012
DOI: 10.1002/pits.21635
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' perceptions of parent–teacher alliance and student–teacher relational conflict: Examining the role of ethnic differences and “disruptive” behavior

Abstract: Although parents' relationships with teachers are considered to be an important aspect of parental school involvement, few studies have examined their implications for students' school adjustment. The present study provided further insight into the relevance of teachers' perceptions of the parent–teacher relationship by examining their link to teachers' perceptions of student–teacher relational conflict. Participants were 36 native Dutch teachers who rated their relationships with 230 Grade 4–6 students (59 Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…The marketisation of education (Corbett & Norwich, 1997;Crozier, 1997), policy change (Tan & Goldberg, 2009) and the school effectiveness movement (Sanders & Epstein, 1998) support parental involvement in children's education. Teacher reports of high-quality parent-teacher relationships are associated with higher levels of child adaptive functioning, lower levels of externalising behaviour (Kim et al, 2013) and less student-teacher conflict (Thijs & Eilbracht, 2012). Higher levels of teacher contact with parents have been associated with increased student academic adjustment at the elementary and middle school levels (Seitsinger et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marketisation of education (Corbett & Norwich, 1997;Crozier, 1997), policy change (Tan & Goldberg, 2009) and the school effectiveness movement (Sanders & Epstein, 1998) support parental involvement in children's education. Teacher reports of high-quality parent-teacher relationships are associated with higher levels of child adaptive functioning, lower levels of externalising behaviour (Kim et al, 2013) and less student-teacher conflict (Thijs & Eilbracht, 2012). Higher levels of teacher contact with parents have been associated with increased student academic adjustment at the elementary and middle school levels (Seitsinger et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A judgement of 'bad' parenting can be made by teachers without any knowledge of actual home life or appreciation of differences in cultural values, lack of time/health and/or financial constraints (Lasky, 2000;Crozier, 1998). Thus, it is not surprising that studies of parent-teacher relationships often find higher-quality relationships between teachers and parents with shared ethnicity, socio-economic status and/or class (Thijs & Eilbracht, 2012;Waanders, Mendez & Downer, 2007;Crozier, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Fishman and Nickerson (2014) tested the Hoover-Dempsey and Sandler model with parents of students receiving special education services and found that the only significant predictor of parent involvement was direct communication from a child's teacher to the parent. According to Thijs and Eilbracht (2012), these direct teacher-parent communications may not only improve the quality of interpersonal bonds between teachers and parents but also allow for the disclosure of child-specific information, which enables teachers to better understand their students' strengths and challenges and to use this understanding to promote student success in the classroom. The other variable found to make a unique and significant contribution to the likelihood of a parent's measure meeting the state standard was a positive statement by the parent regarding the quality of the special education services provided to the child.…”
Section: Discussionmentioning
confidence: 99%
“…Students who are adapting to new mannerisms may appear to be acting out or displaying challenging behavior but may actually be resolving differences between cultures. A study conducted by Thijs and Eilbracht (2012) found that Dutch teachers reported higher conflict with Moroccan-Dutch students; the researchers speculate that the cause is varying or conflicting belief systems. The Moroccan-Dutch are described as a collectivist culture (strong sense of loyalty to the group) and power distant, "implying respect and obedience for authority figures" similar to Western belief systems (p. 797).…”
Section: Rti and Cultural And Linguistic Diversitymentioning
confidence: 99%